Isolation and Characterization of Mammalian Otic Progenitor Cells that Can Differentiate into Both Sensory Epithelial and Neuronal Cell Lineages. Issue 3 (13th January 2020) - Kojima, Ken; Nishida, Akiko T.; Tashiro, Kei; Hirota, Kiichi; Nishio, Takeshi; Murata, Miyahiko; Kato, Nobuo; Kawaguchi, Saburo; Zine, Azel; Ito, Juichi; Van De Water, Thomas R.
ABSTRACT: The mammalian inner ear mediates hearing and balance and during development generates both cochleo‐vestibular ganglion neurons and sensory epithelial receptor cells, that is, hair cells and support cells. Cell marking experiments have shown that both hair cells and support cells can originate from a common progenitor. Here, we demonstrate the lineage potential of individual otic epithelial cell clones using three cell lines established by a combination of limiting dilution and gene‐marking techniques from an embryonic day 12 (E12) rat otocyst. Cell‐type specific marker analyses of these clonal lines under proliferation and differentiation culture conditions demonstrate that during differentiation immature cell markers (Nanog and Nestin) were downregulated and hair cell (Myosin VIIa and Math1), support cell (p27 Kip1 and cytokeratin) and neuronal cell (NF‐H and NeuroD) markers were upregulated. Our results suggest that the otic epithelium of the E12 mammalian inner ear possess multipotent progenitor cells able to generate cell types of both sensory epithelial and neural cell lineages when cultured under a differentiation culture condition. Understanding the molecular mechanisms of proliferation and differentiation of multipotent otic progenitor cells may provide insights that could contribute to the development of a novel cell therapy with a potential to initiate or stimulate the sensorineural repair of damaged inner ear sensory receptors. Anat Rec, 303:451–460, 2020. © 2019 American Association for Anatomy